Pengembangan Potensi Wisata Situ Rancabala di Desa Cimari Kecamatan Cikoneng Kabupaten Ciamis - Vina Dwi Yulianti; Andi Sunardi; Teguh Irianto; Yordan Renaldo Putra (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
The development of community-based tourism in Situ Rancabala, Cimari Village, Cikoneng District, Ciamis Regency has not been carried out sustainably. The purpose of this research is to provide encouragement and motivation to the village government and community in developing the tourism potential of Situ Rancabala, Cimari Village, Cikoneng District, Ciamis Regency. The method used is a qualitative research method with a descriptive approach. Then the data collection techniques in this study were carried out through observation, interviews and documentation. While the data processing techniques in the study were carried out by data collection, data reduction, data presentation and conclusion drawing. The results of the study show that the development of Situ Rancabala's potential in Cimari Village, Cikoneng District, Ciamis Regency has been quite good, this can be seen from the Village Government which continues to make development progress every year, has collaborated with various government agencies. In addition, there are already facilities around Situ Rancabala such as homestays, although they have not been able to operate. The obstacles faced by the Cimari Village Government in developing the potential of Situ Rancabala in Cimari Village are: lack of involvement from the private sector or entrepreneurs who are expected to increase capital for the development of Situ Rancabala. To overcome these obstacles, the Cimari Village Government is making various approaches to related agencies and the private sector to increase collaborative cooperation in helping to develop Situ Rancabala.